Paralelismo de unidades de armazenamento de energia conectadas em uma microrrede c.c - Frederico Luiz Fernandes Marcelino (2017)
Due to the concern with energy demand, energy efciency and the use of renewable resources, the microgrids have stood out in the last years. Both AC and DC microgrids can be used in residential and commercial facilities. In particular, the DC microgrids exhibit advantages over its AC counterpart such as efciency and dispense of phase and frequencycontrol. To provide energy during low energy generation or to smooth out energy balance between generation and demand, energy storage systems are normally employed, being absolutely necessary for islanded mode microgrids. This master thesis includes the topics aforementioned and contributes with a study of paralleling distributed energy storage units in a droop controlled DC microgrid. The Dual= Active Bridge energy storage converters are modeled and the controllers are designed. Forthese converters adaptive droop control are employed, which are modifed according to the state of charge of each battery bank in order to balance state of charge. This work also proposes and analyzes diferent droop compensation functions from those that have been used in literature. Simulation results of case studies are developed in order to investigate the proposed converter performance in a DC microgrid. Results show that converters can operate in parallel, with droop, in both operation modes. The microgrid with excess energy is not investigated.